TERMINAL MANAGEMENT POLICY AND PASSENGER ACCESSIBILITY AT CICAHEUM BUS TERMINAL BANDUNG, WEST JAVA - Sakti, Fajar (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
This research is based on the main problem, namely: accessibility of the Bandung Cicaheum terminal is not optimal. This is thought to be caused by terminal management not yet being implemented. The approach used in this research is terminal management to the accessibility of case study passengers at the Cicaheum terminal. The research method used in this study uses qualitative methods with a case study. On this study, the researcher emphasizes more on investigations to understand social problems, based on respondents detailed views of the problem. The results showed that the dimension of terminal management had not been carried out especially the planning dimension. The change of authority mandates that type A terminals that serve between cities and provinces become the authority of the central government. It has been three years since the mandate of the Law has been carried out over the function of authority, especially the elements of Personnel, Funding, Facilities and Infrastructure, and Documents (P3D). Research findings since the 2019 Budget Year Bandung City Government through the Department of Transportation has no longer allocated the Cicaheum terminal budget. Likewise, accessibility dimension, especially the intensity factor (density) of land use which is no longer suitable with the current conditions. gb777